Start from Zero: Creative Brand Publicity in Pertamina's Ramadan and Eid al-Fitr Television Campaign - Septiani Devi; Dinda Dwi Lestari; Houce Mariano (Jobmark: Journal of Branding and Marketing Communication, 2025)
Creative Brand Publicity (CBP) is a branding approach that relies on innovative narratives, distinctive design, and imaginative concepts to deliver brand messages in ways that capture public attention without depending solely on paid media. As Indonesia's state-owned energy company, Pertamina has long recognized that creative publicity is indispensable for reinforcing brand awareness and corporate image, particularly at moments when the company's activities intersect with matters of public trust, such as the integrity of fuel distribution. One of the company's most enduring publicity efforts is the "Start from Zero" (Dimulai dari Nol) television commercial, first broadcast in 2008 ahead of Eid al-Fitr 1429 H, which dramatized the honesty and courtesy of Pertamina gas-station attendants. This study examines how Pertamina implemented CBP in the "Start from Zero" campaign through the three analytical dimensions proposed by Wijaya (2011): Mood, Moment, and Movement. Using a descriptive-qualitative case-study design, the research draws on document analysis of the television advertisement, social-media postings, comments, online news coverage, and archived screenshots collected over more than a decade of the campaign's continued circulation. The findings show that Brand's Mood Analysis (BMA) and Consumer's Mood Analysis (CMA) both indicate a high level of brand-communication intensity and audience enthusiasm, respectively. From the Moment perspective, Pertamina strategically timed the campaign's release to coincide with the religious and cultural significance of Ramadan and Eid al-Fitr, strengthening its emotional resonance. From the Movement perspective, the campaign's tagline evolved into a self-sustaining cultural meme that continues to circulate across social media, blogs, and news outlets long after its original broadcast. The study contributes to the theoretical understanding of CBP as an integrative branding framework and offers practical insight into how timing, narrative authenticity, and multichannel amplification can transform a routine corporate advertisement into a long-lasting publicity asset.